Seafood Consumption Attributes and Buying Behaviours According to the Generations: A Study on Millennial Generation in Turkish Market - Osman İnanç Güney; Levent Sangün (Turkish Journal of Agriculture: Food Science and Technology)
This paper focus on the seafood consumption attitudes and behaviours of the millennials (Generation Y) and non-millennials (Generation X, Baby Boomers and Silent Generation) comparatively. The data was collected from a face to face survey which was applied to randomly select 407 individuals in the city of Adana, Turkey in November 2016. As a result of factor analysis applied in the study, it was found that Millennials was significantly and inversely correlated with consumption of wild fish and freshwater fish. Non-millennial generation was inversely correlated with consumption of marine fish, freshwater fish and mussels and the correlation is insignificant. According to the results of the chi square test, it was determined that Millennials mostly preferred to consume fresh (unprocessed) fish. Mann-Whitney test results show that they value health and nutrition factors for consumption and there is a significant difference between these two factors. Besides, factors mainly effecting their purchase behaviour of seafood are directed to freshness, seasonality, place of purchase and wild-aquaculture product classification and there are significant differences between these factors. The fact that the Millennial’s average response to consumption and purchasing is higher indicates that they are more cautious.